The information sources used by Sri Lankan youths: A survey - Thushanika, P.; Sirikanth, S. (University of Jaffna, 2022)
Data and information play a significant role in the functioning of the world. Out of the total population, 4.64 million (23.2%) are youths in Sri Lanka, playing an essential role in the economic, political, educational, and other sectors. Against this backdrop, this study aims to identify the information-gathering sources used by youths in Sri Lanka. This study adopts a quantitative research approach and collects primary data using an online questionnaire (google form) with 500 Youths island-wide through a convenient sampling method. According to the findings, 81.7% of youths use the internet as their primary source of information, and all ethnicity youths use it significantly (µ> 7). 79.3% of youths use social media for information gathering, including Facebook, and Sinhalese youths (µ=7.34) are the most active among the ethnic group. Television is watched by 63.8% of them, with Indian Tamil youths (µ=5.94) watching the most. 56.4% actively seek information from friends and family. This phenomenon is higher among Indian Tamils and Moors than in other communities. 49.5% listen to the radio infrequently, while Indian Tamils (µ=5.73) listen to it regularly for information. 34.38% read the daily newspaper frequently, whereas others read it occasionally. 28.2% of youths are using tea stalls for collecting and exchanging information. 70.8% of youngsters are not interested in attending political or religious gatherings to obtain information. A significantly lower per centage of youths are identified in the Sinhala community (µ=2.83). Youths should concentrate on traditional methods of gathering information and be aware of internet access and safety mechanisms in Sri Lanka. Youths need to identify the ways which help to get quality and reliable information for critical thinking and work effectively for their development. Effective Information policies and qualities are vital to the country’s sustainable development through an Information Management System.
Keywords: Information sources; Youths; Internet; Social media